PERLINDUNGAN BURUH MIGRAN FILIPINA DALAM KONSTITUSI - Ditta Giarni Martha (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
The Philippines is a country that has a good migrant worker management system. Based on Article 13 of the Philippine Constitution states that the state through the authority of the Human Rights Commission guarantees appropriate legal action for the protection of the human rights of all people in the Philippines as well as Filipinos working abroad. The research method in this paper uses the normative legal research method. This research method is a method that uses and analyzes written regulations which are closely related to the library. The research result of this paper is that the POEA is fully responsible to its President through the Minister of Manpower. The POEA's relationship with other institutions related to the protection of migrant workers is sub-coordinative. POEA is the mother for the protection of migrant workers. Legal protection agencies or agencies for migrant workers in the Philippines are maximizing the roles of the Philipine Overseas Employment Agency (POEA), Overseas Workers Welfare Administration (OWWA) and The Office of the Legal Assistant for Migrant Affairs (OLAMA). Where the POEA is assigned to monitor and supervise recruitment agencies in the Philippines, the OWWA provides Filipino migrant workers and their families with all the assistance they may need in enforcing contractual obligations by agencies or agencies and / or their principals, and OLAMA has the duty and authority to assist and protect who get unfair treatment, both physically and psychologically.